Impact of weather variables and season on sporulation of Phytophthora pluvialis and Phytophthora kernoviae. Issue 2 (3rd March 2020) - Fraser, Stuart; Gomez‐Gallego, Mireia; Gardner, Judy; Bulman, Lindsay S.; Denman, Sandra; Williams, Nari M.
Abstract: Phytophthora pluvialis and Phytophthora kernoviae are the causal agents of important needle diseases on Pinus radiata in New Zealand. Little is known about the epidemiology of the diseases, making the development of control strategies challenging. To investigate the seasonality and climatic drivers of sporulation, inoculum traps, consisting of pine fascicles floating on water in plastic containers, were exchanged fortnightly at five sites in P. radiata plantations between February 2012 and December 2014. Sections of needle baits were plated onto selective media and growth of Phytophthora pluvialis and P. kernoviae recorded. To explore the generalizability of these data, they were compared to detection data for both pathogens from the New Zealand Forest Health Database (NZFHDB). Further, equivalent analyses on infection of Rhododendron ponticum by P. kernoviae in Cornwall, UK allowed the comparison of the epidemiology of P. kernoviae across different host systems and environments. In New Zealand, inoculum of P. pluvialis and P. kernoviae was detected between January–December and March–November, respectively. Inoculum of both species peaked in abundance in late winter. The probability of detecting P. pluvialis and P. kernoviae was greater at lower temperatures, while the probability of detecting P. pluvialis also increased during periods of wet weather. Similar patterns were observed in NZFHDB data. However, the seasonal pattern of infection by P. kernoviae in the UK was the opposite of that seen for sporulation in New Zealand. Phytophthora kernoviae was likely limited by warmer and drier summers in New Zealand, but by colder winter weather in the UK. These results emphasize the importance of considering both environmental drivers and thresholds in improving our understanding of pathogen epidemiology.